Trematode community of tadpoles and adult anurans from Cerrado, Brazil: Morphological and ecological aspects - Queiroz, M.S. [UNESP]; Delgado, M.L.R. [UNESP]; Pinto, H.A.; Anjos, Luciano Alves dos (Cambridge University Press (CUP), 2025)
Anurans are bioindicators and key components of ecosystem functions. Although South America harbors more than 4,000 identified anuran species, fewer than 10% have been analyzed regarding their trematode fauna. When tadpoles are considered, the paucity of studies becomes even more evident. Considering the ability of digeneans to serve as indicators of ecosystem health, it is evident that there is a gap in the knowledge of trematodes occurring in anuran biodiversity hotspots. Herein, we provide an ecological and morphological analysis of the trematode component community recovered in tadpoles and adult anurans. During a long-term herpetological and helminthological study conducted in a Cerrado fragment in Brazil, 569 anurans from 17 species were necropsied. Eleven species were common to both adults and tadpoles, and six species occurred only in adults. The total prevalence was 61% (352/569), in separate analyses, 65% (192/296) for adult anurans, and 58% (160/273) for tadpoles. A total of 12,397 trematodes belonging to 16 taxa were recovered. The component community was composed mostly of metacercariae. We provided a brief morphological description for each trematode taxa recovered. Additionally, statistical analysis was performed to elucidate the differences between tadpoles and adult anurans trematode communities. The trematode community analyzed in our study revealed 24 new host records and was the first to include tadpoles in such an analysis, highlighting the importance of faunistic inventories for a better understanding of parasitism in their hosts, as well as providing a foundation for further research.